Yes‐associated protein 1 promotes the differentiation and mineralization of cementoblast. Issue 3 (25th September 2017) - Yang, Beining; Sun, Hualing; Song, Fangfang; Wu, Yanru; Wang, Jiawei
Abstract : Yes‐associated protein 1 (YAP1) transcriptional coactivator is a mediator of mechanosensitive signaling. Cementum, which covers the tooth root surface, continuously senses external mechanical stimulation. Cementoblasts are responsible for the mineralization and maturation of the cementum. However, the effect of YAP1 on cementoblast differentiation remains largely unknown. In this study, we initially demonstrated that YAP1 overexpression enhanced the mineralization ability of cementoblasts. YAP1 upregulated the mRNA and protein expression of several cementogenesis markers, such as alkaline phosphatase (ALP), runt‐related transcription factor 2 (Runx2), osteocalcin (OCN), and dentin matrix acidic phosphoprotein 1 (DMP1). The YAP1 overexpression group showed higher intensities of ALP and Alizarin red stain than the YAP1‐knockdown group. Unexpectedly, a sharp increase in the expression of dentin sialophosphoprotein (DSPP) was induced by the overexpression of YAP1. Knockdown of YAP1 suppressed DSPP transcriptional activity. YAP1 overexpression activated Smad‐dependent BMP signaling and slightly inhibited Erk1/2 signaling pathway activity. Treatment with specific BMP antagonist (LDN193189) prevented the upregulation of the mRNA levels of ALP, RUNX2, and OCN, as well as intensity of ALP‐stained and mineralized nodules in cementoblasts. The Erk1/2 signaling pathway inhibitor (PD 98, 059) upregulated these cementogenesis markers. Thus, our study suggested that YAP1 enhanced cementoblast mineralization in vitro. YAP1 exerted its effect on the cementoblast partly by regulating the Smad‐dependent BMP and Erk1/2 signaling pathways. Abstract : YAP1 enhanced cementoblast mineralization in vitro. YAP1 exerted its effect on the cementoblast partly by regulating the Smad‐dependent BMP and Erk1/2 signaling pathways.